2017
DOI: 10.1002/bse.1979
|View full text |Cite
|
Sign up to set email alerts
|

Substantive or Symbolic Environmental Strategies? Effects of External and Internal Normative Stakeholder Pressures

Abstract: Different forms of stakeholder pressures drive different environmental strategies in organizations. This article differentiates between internal and external normative stakeholder pressures to test their potentially unique effects on environmental strategies. The findings suggest that internal, normative stakeholder pressures primarily drive substantive commitments to environmental practices, reflecting an internalized, voluntary commitment to the natural environment and dedication to environmental leadership … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
140
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(144 citation statements)
references
References 137 publications
(216 reference statements)
4
140
0
Order By: Relevance
“…Finally, Hyatt and Berente () found that internal stakeholder pressures often primarily drive substantive commitments to environmental practices, whereas external pressures primarily drive symbolic commitments to environmental practices. Because shareholders have the unique position of being both internal (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, Hyatt and Berente () found that internal stakeholder pressures often primarily drive substantive commitments to environmental practices, whereas external pressures primarily drive symbolic commitments to environmental practices. Because shareholders have the unique position of being both internal (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Liao and Tsai () suggested that stakeholder pressure consists of two primary sources: environmental regulations, which refer to regulations enacted by governments to protect or improve the environment, and green customer needs, which describe the market demand for green products and services. Stakeholder pressure is identified as an important external contextual factor that influences the performance impacts of green knowledge sharing (Hyatt & Berente, ). However, existing findings are inconsistent, ranging from a positive effect (Liao & Tsai, ; Tsai & Liao, ) to no effect (Zhu & Zhu & Sarkis, ), indicating that the mediating mechanism through which the benefits of green knowledge sharing transform into green innovation remains to be identified.…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…Third, a supply chain perspective helps us understand how an environmental NGO selects commercial organizations to be held accountable (e.g., extended producer responsibility; Hickle, ) for hotspots, or to collaborate with to drive change via market mechanisms (e.g., eco‐certifications). SCM scholars have begun to take account of the pressures exerted, or opportunities provided, by civil society stakeholders such as environmental NGOs on organizations to improve supply chain practices with respect to environmental impacts as well as a host of social impacts (Hyatt & Berente, ; Sarkis, Gonzalez‐Torre & Adenso‐Diaz, ; Wolf, ). While traditionally these environmental NGOs operated from an activist perspective, many now go beyond activism to collaboratively engage corporate actors in supply chains in building awareness and identifying impacts for improvement and in some cases helping firms to implement more sustainable practices (Hyatt & Johnson, ; McDonald & Young, ; Meixell & Luoma, ).…”
Section: Relevance Of Ngo Supply Chainsmentioning
confidence: 99%